Determination of Ku-band specific attenuation parameters based on measurements in the tropics - Ismail, Ahmad Fadzil; Badron, Khairayu; Yaccop, A.A.H.; Yao, Y.D. (2013)
Attenuation due to rain is a critical constraint in the design of Earth-space links especially at frequencies higher than 10 GHz. Rain attenuation prediction models proposed by ITU-R were reported to offer good estimation for temperate regions but a number of studies reveal that it severely underestimates the concerned signal in the tropics. The study attempted to derive new applicable specific attenuation coefficients using one-year 11 GHz satellite beacon data and rainfall rate measurements in Malaysia. The acquired outcomes are incorporated in the ITU-R procedure to assess their suitability and significance